Hyperlipidemia Preventing Activities of Standardized Ethanolic Extract of Red Spinach (Amaranthus tricolor L.): An In Vivo Study in Male Sprague-Dawley Rats - Pradana, Dimas Adhi; Apriani, Lalily; Widyarini, Sitarina (Pusat Penelitian dan Pengembangan Biomedis dan Teknologi Dasar Kesehatan, 2018)
Lipid metabolism disorders can lead to hyperlipidemia that triggers atherosclerosis. This study aimed to identify the potential of standardized ethanolic extract of red spinach (Amaranthus tricolor L.) to prevent hyperlipidemia by referring to the reduction of triglyceride level and total cholesterols in male Sprague-Dawley rats. A total of 30 experimental animals was put into 6 groups, including normal, positive control (0.9 mg/kgBW of simvastatin), negative control, treatment I (200 mg/kgBW of extract), treatment II (400 mg/kgBW of extract), and treatment III (800 mg/kgBW of extract). Preventive therapy and positive control were administered from day 1 to day 67. Hyperlipidemia was induced by feeding pure lard and duck yolk to the rats twice daily from day 8 to day 67. Determination of triglyceride level and total cholesterols was conducted on day 0 and day 67. The findings revealed that the treatment groups with ethanolic extract of red spinach at doses of 200 mg/kgBW, 400 mg/kgBW, and 800 mg/kgBW had statistically significant differences (p